The Patients' Perspective: Hematological Cancer Patients' Experiences of Adverse Events as Part of Care. Issue 5 (17th August 2021) - Bryant, Jamie; Carey, Mariko; Sanson-Fisher, Rob; Turon, Heidi; Wei, Andrew; Kuss, Bryone
Abstract : Objective: To describe in a sample of patients with a confirmed diagnosis of a hematological cancer: (a) the proportion who self-report experiencing an unexpected adverse event as part of their care; (b) how the adverse event was handled by the health-care organization; and (c) the sociodemographic, disease, and treatment characteristics associated with experiencing an adverse event. Design: Cross sectional survey. Setting: Three Australian hematological oncology treatment centers. Participants: Individuals with a confirmed diagnosis of a hematological cancer. Main Outcome Measures: Participants were asked if they had ever experienced an adverse event in their cancer care. Those who did were asked about their perceptions concerning what the adverse event was related to, how much harm the event caused, who identified the adverse event, and how the health-care organization responded to the adverse event. Results: Forty-two participants (26.4%) perceived that they had experienced an unexpected adverse event as part of their care. Most were told about the event as soon as it happened (62%) and were given an explanation about why the event occurred (75%). Fewer were given information about how to take the matter further if they wished (43%). Participants who were unemployed, retired, disabled, or performed home duties and those whose employment status was "other" had higher odds of reporting an adverse event than those in full- or part-time employment. Conclusions: There is a need for routinely querying patients during their treatment regarding the occurrence of unexpected adverse events. In addition, there is a need for improvement in the responses of health-care providers and the health-care system to these events in regard to full disclosure, apology, and options available to the patient for resolution.